Seawater intrusion vulnerability assessment by Galdit method in the Metaponto coastal aquifer (Basilicata, Italy) - Muzzillo, Rosalba; Canora, Filomena; Polemio, Maurizio; Sdao, Francesco (Italian journal of engineering geology and environment, 2022)
The groundwater vulnerability assessment to seawater intrusion (SWI), applying the GIS-based overlay-index GALDIT method, is provided for the Metaponto coastal aquifer (Basilicata region, southern Italy). The method is based on six conditioning parameters: groundwater occurrence (G), aquifer hydraulic conductivity (A), groundwater level (L), distance from the shore (D), impact of the existing status of SWI (I), and aquifer thickness (T). Three vulnerability classes were detected: low, moderate, and high, covering 70.40%, 22.65%, and 6.95% of the study area, respectively. The highest class is located close to the coastal sector due to the proximity to the sea, the greater thickness of the aquifer, and the shallow freshwater-seawater interface. To evaluate the sensitivity of the method on the predictive analysis and the influence of the single parameter and weight on the final vulnerability, the sensitivity analysis was carried out. The single-parameter analysis indicated that the factors such as groundwater table above sea level (a.s.l.), aquifer type, and impact of SWI have the greatest influence on the vulnerability. The application leads to the vulnerability mapping to SWI in the coastal plain that results to be a promising tool for decision-making finalized to properly manage groundwater.